2014
DOI: 10.1016/j.conbuildmat.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Crack initiation in asphalt mixtures under external compressive loads

Abstract: h i g h l i g h t sA crack initiation criterion is derived for asphalt mixtures in compression. Bond energy increases with aging and loading rate and decreases with temperature. Percentages of cohesive and adhesive cracking are determined for asphalt mixture. Compressive strength is predicted by simplified crack initiation criterion. a b s t r a c tCrack initiation was studied for asphalt mixtures under external compressive loads. High tensile localized stresses e direction of the external loads. A quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 46 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…Recently, Li and Greenfield [23,24] However, limited work has been focused on the effects of bitumen's oxidative aging on the adhesion of the bitumen-mineral interface at the molecular scale, particularly when the minerals are different and water are present. The authors' previous studies have found that the interfacial adhesion between the bitumen and aggregate played a critical role in determining the viscoelastic characteristics and cracking performance of the asphalt mixtures [27][28][29][30][31]. The interfacial interaction between bitumen and mineral surfaces has been investigated using…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, Li and Greenfield [23,24] However, limited work has been focused on the effects of bitumen's oxidative aging on the adhesion of the bitumen-mineral interface at the molecular scale, particularly when the minerals are different and water are present. The authors' previous studies have found that the interfacial adhesion between the bitumen and aggregate played a critical role in determining the viscoelastic characteristics and cracking performance of the asphalt mixtures [27][28][29][30][31]. The interfacial interaction between bitumen and mineral surfaces has been investigated using…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(1) When the load cycle is zero (N = 0), c is equal to the average air void size, which has a regression relation with the air void content as follows [30]:…”
Section: Assessment Of Field Fatigue Performancementioning
confidence: 99%
“…ΔG = bond energy of the asphalt mixture, which represents a combined bond energy for cohesive fracture and adhesive fracture. A higher temperature or a lower loading rate induces more percentage of cohesive fracture and therefore leads to a lower bond energy (4). The temperature and rate dependent bond energy for an asphalt mixture is modelled as:…”
Section: Viscofracture (Vf)mentioning
confidence: 99%
“…11,12,16,19,and 24). The authors have also presented systematic testing and data analysis methods in previous studies to determine the material properties and model parameters, details of which are not repeated in this paper but referred to the publications (4,5,17,25,37). Four asphalt mixtures were selected to validate the VEPF models and the weak form PDE based FE modeling.…”
Section: Materials Properties As Model Inputsmentioning
confidence: 99%